Awareness and Attitudes Towards Open Access Predatory Publications Among the Academic Staff Members of Faculty of Management Studies and Commerce, University of Jaffna, Sri Lanka - Janen, T. (University Librarians Association of Sri Lanka, 2024)
The scholarly community is now dealing with a serious issue with predatory journals. It might be difficult for authors to identify predatory publications apart from reputable ones. The purpose of this study is to investigate the academic staff members of the Faculty of Management Studies and Commerce, University of Jaffna, Sri Lanka on awareness of predatory publications and open access. The research methodology used in this study to gauge participants' knowledge of "open access" and "predatory publishing" was a questionnaire survey. Data collection involved the use of a pretested questionnaire. The permanent academic staff members affiliated with the Faculty of Management Studies and Commerce, university of Jaffna comprised the study's population. A link to an online survey was shared with every one of the faculty's fifty-two academic staff members. The response rate of the study was 67.30 %. MS Excel was used for the data analysis to describe the data in frequencies, percentages and rank orders of responses.Socio demographic details shows that, highest number of respondents are female (57.14%), completed master/MPhil (51.42%), senior lecturer (57.14%) and interested in marketing (28.57%) as their research discipline. Respondents expressed their priority order for the factors considered to select journal to submit manuscript for publications, journal indexing is the highest priority. All the respondents have an idea about the open access publishing system. Respondents are expected to publish in open access journals because of high visibility, increasing citation number, prestigious journals and fast publication process in a frequency order. The result of the survey shows that, 97.15% of the respondents are knowledgeable about predatory publishing. Majority of the respondents are characterized, the predatory journals are, no insufficient peer review process, and Beall’s list of predatory journals used by the high number of respondents to differentiate legitimate journals from predatory journals. More than half of the respondents are satisfied with the services provided by the library to avoid publishing in predatory journals. Responses are summarized for each of the 8 statements about the impact of publishing in predatory journals. Almost all the statements are agreed by the respondents other than the statement of “Articles published in predatory journals are poor in quality”. Highest agreement found for the statement 3 which is “Predatory publications are not considered for any academic reward” in which 14out of 35 were strongly agreed and followed by the statement 2 “many researchers published articles due to lack of awareness about predatory publication” (13 out of 35). Finally respondents are suggested to organize more awareness session on open access publishing and journal selection to avoid predatory publishing.
Keywords: Predatory journals; Open access publishing; Open access journals; Awareness of predatory journals; Publication ethics